4(3x-3)=5(x+3)

Simple and best practice solution for 4(3x-3)=5(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-3)=5(x+3) equation:



4(3x-3)=5(x+3)
We move all terms to the left:
4(3x-3)-(5(x+3))=0
We multiply parentheses
12x-(5(x+3))-12=0
We calculate terms in parentheses: -(5(x+3)), so:
5(x+3)
We multiply parentheses
5x+15
Back to the equation:
-(5x+15)
We get rid of parentheses
12x-5x-15-12=0
We add all the numbers together, and all the variables
7x-27=0
We move all terms containing x to the left, all other terms to the right
7x=27
x=27/7
x=3+6/7

See similar equations:

| -18=-4x+2(3x=3) | | (6p+1)(2)= | | -10=-4+4x | | 44=4d | | 6x=2(-2x-4)=-30 | | 14x-(7x-5)=47 | | 7w+28=14w | | 9−2b=-b | | 6p^2=48p=90 | | 1=d-6 | | 9(4x-3)=99x | | -20−5−7n=19−18n | | .40=g/22+0.146 | | 3=3x+2(-x-2) | | 3x+15+11x-5/2=47 | | 10+9j=7j | | 11(x+3)=5(3x+1) | | 4.6b=13.68+7b | | 5y+8-4y=3y-12 | | 17+13s=14s | | 11c+13+13=-16+17c | | -5=2x-3(x-2) | | -10u-20=-12u+14 | | 10-7z=-8-5z | | 2d-6=d | | -5x-4(-2x-2)=-10 | | 1/2(t-12)=4 | | h-10=10-9h+10 | | -20=-4/7v | | 6+u/2=-2 | | 4r-10=r+8 | | 4w-7=-3 |

Equations solver categories